The BASES Expert Statement on protein recommendations for athletes: amount, type and timing - Morgan, P.; Killer, S.; Macnaughton, L.; Dirks, M.; Witard, O.; Wall, B.; Breen, L. (The Sport and Exercise Scientist, 2022)
The topic of protein nutrition is continually evolving, with much interest focussed on recommendations for athletes. From an applied perspective, each of the 4000+ meals consumed across an Olympic cycle (assuming 3 meals/day) provides an opportunity for dietary protein to support recovery, adaptation and/or athletic performance. This expert statement presents concise, evidence- based, and practically relevant protein recommendations for athletes.